2002
DOI: 10.1021/la025785w
|View full text |Cite
|
Sign up to set email alerts
|

OH Surface Density of SiO2 and TiO2 by Thermogravimetric Analysis

Abstract: Thermogravimetric analysis (TGA) is investigated for determination of the OH surface density (OH/ nm 2 ) and carbon content of silica and titania powders made by flame aerosol and sol-gel processes. It is shown that it is possible to distinguish between physically adsorbed and chemically bound water and to rapidly determine the OH surface density even of small powder samples (<0.2 g) by TGA calibrated with LiAlH 4 titration data. The high accuracy of the OH surface density determination by TGA is confirmed fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
399
3
14

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 486 publications
(446 citation statements)
references
References 17 publications
30
399
3
14
Order By: Relevance
“…According to reports in the literature, 40,41 physically adsorbed water can be removed at 120 1C, indicating that weight loss above 120 1C resulted from the removal of hydroxyl groups on the ZrO 2 -NC surface. Weight loss could potentially arise from the desorption of volatile organic compounds left from particle processing; however, FT-IR spectra (Figure 1a) confirmed that there were no volatile organic compounds on the particles.…”
Section: Transparent Hybrid Materials With Inorganic Nanoparticles T mentioning
confidence: 86%
“…According to reports in the literature, 40,41 physically adsorbed water can be removed at 120 1C, indicating that weight loss above 120 1C resulted from the removal of hydroxyl groups on the ZrO 2 -NC surface. Weight loss could potentially arise from the desorption of volatile organic compounds left from particle processing; however, FT-IR spectra (Figure 1a) confirmed that there were no volatile organic compounds on the particles.…”
Section: Transparent Hybrid Materials With Inorganic Nanoparticles T mentioning
confidence: 86%
“…10,11 The thermogravimetric analysis (TGA) curves (not shown) of the carbon-titania powders showed a slight decrease of 0.5-1 wt.% when heating up the powders from 120 to 800°C under nitrogen atmosphere followed by a rapid weight loss (0.5-52 wt.%, depending on the C-content) when switching the atmosphere to oxygen at 800°C. The former weight loss can be attributed to removal of chemisorbed water, surface OH-groups and any volatile organic compounds, while the latter is directly related to non-volatile carbon (soot) oxidation and removal as CO 2 or CO. 5,16 The sample weight remains constant when further heating the powder to 1000°C, since the TiO 2 surface is free of OH groups at this temperature. 16 Figure 3 shows TEM pictures of the carbon-titania powders containing (a) 15 wt.% and (b) 52 wt.% carbon, respectively, as well as HRTEM of the corresponding powders (c) 15 wt.% and (d) 52 wt.%.…”
Section: Hk Kammler Et Almentioning
confidence: 99%
“…In the case of the modified clinoptilolites, be given to this profile should be related to dehydroxilation; since this process, in zeolites [6] and silica [51], produces the condensation of the OH groups. In the particular case of zeolites is generally accepted that during the process of dehydroxylation at temperatures up to 500 °C, bridged hydroxyls condenses to produce water and left behind the zeolite framework negatively charged [52], trigonal aluminum [53] and different types of positively charged extra-framework aluminum [54], at higher temperatures a dehydrogenation process is as well produced [55].…”
Section: Resultsmentioning
confidence: 99%